Alternative Waqf Model for SDG-4 (Quality Education) - Rusydiana, Aam Slamet (SMART Insight, 2023)
This study aims to determine the opinions and recommendations of experts regarding the waqf model integrated with sustainable development (SDGs) in the fourth goal, namely quality education. This research will explain the priority of the waqf model in achieving SDG 4 goals by considering Maqashid Syariah indicators. This research is conducted using primary data in the form of weighting questionnaire results from experts consisting of academics, practitioners and regulators with a background in Islamic economics. The data were analyzed using the Delphi method to find the main priorities and agreement of the experts. The results showed that in the SDGs aspect, the social element was the top priority with an average value of 8.07. In the maqashid sharia aspect, the element of preserving the intellect (aql) is the top priority with an average score of 8.33. As for the waqf model aspect, the Waqf & Zakat model is the top priority with an average score of 8.07. This research can be used as a reference in the implementation of waqf models that can support the realization of the fourth goal of SDGs by considering Maqashid Sharia with priorities according to the findings. This research is the first to comprehensively calculate the experts' assessment of the waqf model for the achievement of SDG 4 using the Delphi method and its priority recommendations.